ADAPTION OF "MEGA EVENT IMPACT SCALE": VALIDITY AND RELIABILITY STUDY (2011 ERZURUM 25. WINTER UNIVERSIADE) - Kerem Yıldırım Şimşek (Pamukkale University, 2012)
This study aims at carrying out validity and reliability studies and the adaption of Turkish version of the scale titled "Mega Event Impact Scale" and developed by Jie ve Yan (2010). The scale, which consists of five-point Likert scale 42 items, was administered to the local audience following 2011 Erzurum 25. Winter Universiade. The subjects of the study were 412 people (55 % male and 45 % female), who were chosen through random sampling method. Explanatory factor analysis, applied to determine construct validity of the scale, revealed a construct with 36 items and 8 factors. The internalconsistency reliability coefficient for the whole study was found 0.917. The findings showed that internal consistency reliability of factor items had an item / total correlation coefficient ranging between 0.50 and 0.85. The results were discussed in terms of the validity and reliability of the Turkish version of the scale.